2015
DOI: 10.1017/s1751731114002651
|View full text |Cite
|
Sign up to set email alerts
|

Effects of γ-aminobutyric acid on feed intake, growth performance and expression of related genes in growing lambs

Abstract: This study was conducted to investigate the effects of rumen-protected γ-aminobutyric acid (GABA) on feed intake, growth performance and expression of related genes in growing lambs. A total of 24 lambs weaned at age of 50 days were divided into four block of six based on their BW, six lambs within a block were allocated to three pairs, which were then assigned randomly to three treatments with addition of rumen-protected GABA at levels of 0, 70 or 140 mg/day for 6 weeks. Dry matter intake was recorded weekly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Similarly, Wang et al. () found that dietary addition of RP‐GABA (at levels of 70 or 140 mg/day for 6 weeks without heat stress) increased only DM intake in growing lambs. This might be somehow attributed to differences in animal type and stage of production (e.g., dairy or beef, lactating or nonlactating), RP‐GABA doses, experimental diet and environment temperature.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Similarly, Wang et al. () found that dietary addition of RP‐GABA (at levels of 70 or 140 mg/day for 6 weeks without heat stress) increased only DM intake in growing lambs. This might be somehow attributed to differences in animal type and stage of production (e.g., dairy or beef, lactating or nonlactating), RP‐GABA doses, experimental diet and environment temperature.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, Cheng et al (2014) indicated that supplementation of RP-GABA (at levels of 40, 80 or 120 mg true GABA/kg BW with heat stress) had increased DM intake but no effect on feed efficiency and apparent digestibility of DM, organic matters, CP, NDF and ADF in heat-stressed lactating dairy cows. Similarly, Wang et al (2015) found that dietary addition of RP-GABA (at levels of 70 or 140 mg/day for 6 weeks without heat stress) increased only DM intake in growing lambs. This might be somehow attributed to differences in animal type and stage of production (e.g., dairy or beef, lactating or nonlactating), RP-GABA doses, experimental diet and environment temperature.…”
Section: Serum Biochemical Parameters Antioxidant Enzyme Activitiementioning
confidence: 80%
“…Glutamate will be converted into GABA if broilers were under stress. According to Wang et al (2015) and Lener et al (2017) GABA served to reduce stress so that it can maintain appetite and increase the efficiency of the use of body nutrients in livestock. Thus giving glutamate to broiler chickens can reduce stress by increasing feed consumption.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were deposited into lithium-heparin-containing vacuum tubes (5 mL, Becton Dickinson, Franklin Lakes, NJ), centrifuged at 3000 × g for 15 min to collect the plasma, and frozen at -20°C for subsequent analysis. Plasma samples were analyzed using an Auto Analyzer 7020 instrument (Hitachi High-technologies Corporation, Tokyo, Japan) with colorimetric commercial kits (Ningbo Medical System Biotechnology Co., Ltd.) to determine total protein, albumin, globulin, BUN, creatinine, glucose, non-esteri ed fatty acid (NEFA), β-hydroxybutyrate, triglyceride, total bilirubin, alkaline phosphatase, aspartate aminotransferase, alanine aminotransferase, insulin, glucagon, pyruvate, LDH and NADH, according to previously described methods [16]. The superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) were determined using the ELISA method by Jiangsu MeiBiao Biological Technology Co., Ltd, Jiangsu, China [17].…”
Section: Sample Collection and Measurementsmentioning
confidence: 99%